The Role of Tryptophan-Kynurenine in Feather Pecking in Domestic Chicken Lines - Birkl, Patrick; Chow, Jacqueline; Forsythe, Paul; Gostner, Johanna M.; Kjaer, Joergen B.; Kunze, Wolfgang A.; McBride, Peter; Fuchs, Dietmar; Harlander-Matauschek, Alexandra (Frontiers in Veterinary Science, 2019)
Research into the role of tryptophan (TRP) breakdown away from the serotonergic to the kynurenine (KYN) pathway by stimulating the brain-endocrine-immune axis system interaction has brought new insight into potential etiologies of certain human behavioral and mental disorders. TRP is involved in inappropriate social interactions, such as feather-destructive pecking behavior (FP) in birds selected for egg laying. Therefore, our goal was to determine the effect of social disruption stress on FP and the metabolism of the amino acids TRP, phenylalanine (PHE), tyrosine (TYR), their relevant ratios, and on large neutral amino acids which are competitors with regard to their transport across the blood-brain barriers, at least in the human system, in adolescent birds selected for and against FP behavior. We used 160 laying hens selected for high (HFP) or low (LFP) FP activity and an unselected control line (UC). Ten pens with 16 individuals each (4 HFP birds; 3 LFP birds; 9 UC birds) were used. At 16 weeks of age, we disrupted the groups twice in 5 pens by mixing individuals with unfamiliar birds to induce social stress. Blood plasma was collected before and after social disruption treatments, to measure amino acid concentrations. Birds FP behavior was recorded before and after social disruption treatments. HFP birds performed significantly more FP and had lower KYN/TRP ratios. We detected significantly higher FP activity and significantly lower plasma PHE/TYR ratios and a trend to lower KYN/TRP ratios in socially disrupted compared to control pens. This might indicate that activating insults for TRP catabolism along the KYN axis in laying hens differs compared to humans and points towards the need for a more detailed analysis of regulatory mechanisms to understand the role of TRP metabolism for laying hen immune system and brain function.